Analyses of the Tourism Potentials of Dala Hill, Kano Metropolis: Protecting Heritage Properties and Promoting Sustainable Tourism - Hafeez Idowu Agbabiaka; Aliyu Salisu Barau; Omotayo Ben Olugbamila; Said Shehu Ibrahim (Journal of Tourismology)
The relationship between human and the Built environments in its complex nature evolved series of consequences as loss of heritage properties through decay, natural hazard, human factors in the modern society. Hence, this study analyzed the heritage tourism potentials of Dala Hill, Kano Metropolis, Nigeria. Both qualitative and quantitative data was collected through detailed inventory and profiling of the site and questionnaire administration on two categories of respondents (above 60years (Aged) and Between 18 – 59years (Agile)) within 300meters vicinity to the site. Therefore, 45 (Aged) people were selected using snowballing sampling procedure, and 262 (Agile) respondents were surveyed using systematic sampling procedure. Findings revealed that Dala hill is faced with the threats of neglect, decay and deterioration induced through weathering and human activities. It has poor sanitary conditions, open defecation, waste disposal, poor accessibility, and is an abode for hoodlums. However, resident perceived the site to generate more economic (RPI = 3.38) and sociocultural (RPI = 3.27) importance, and moderate environmental (RPI = 3.18) importance in the study area if necessary, attention, restoration and transformation plan are designed and implemented.